2019
DOI: 10.1017/s0950268819001900
|View full text |Cite
|
Sign up to set email alerts
|

Impact of mechanical ventilation on the daily costs of ICU care: a systematic review and meta regression

Abstract: The impact of mechanical ventilation on the daily costs of intensive care unit (ICU) care is largely unknown. We thus conducted a systematic search for studies measuring the daily costs of ICU stays for general populations of adults (age ≥18 years) and the added costs of mechanical ventilation. The relative increase in the daily costs was estimated using random effects meta regression. The results of the analyses were applied to a recent study calculating the excess length-of-stay associated with ICU-acquired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 26 publications
(43 reference statements)
0
26
0
Order By: Relevance
“…The first study, a meta-regression analysis, showed that iMV substantially increased daily ICU costs by 25% and suggested that LOS is likely to be an important contributor to the iMV cost component. 5 However, that study not only noted the paucity of information available on the economic impact of iMV, but also appeared to focus on duration of LOS as an effect of ventilator-assisted pneumonia. That focus is in contrast to the current study, which considered use of iMV as treatment for a primary diagnosis of pneumonia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first study, a meta-regression analysis, showed that iMV substantially increased daily ICU costs by 25% and suggested that LOS is likely to be an important contributor to the iMV cost component. 5 However, that study not only noted the paucity of information available on the economic impact of iMV, but also appeared to focus on duration of LOS as an effect of ventilator-assisted pneumonia. That focus is in contrast to the current study, which considered use of iMV as treatment for a primary diagnosis of pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these patients require an extended length-of-stay (LOS) and therapy that often necessitates management within the setting of an intensive care unit (ICU), including the need for invasive mechanical ventilation (iMV), [2][3][4] which has previously been suggested to be a major driver of ICU costs for other disease states. 5,6 Current responses to the immediate need for care of COVID-19 patients include a renewed focus on existing management strategies that may be appropriately applied to these patients and rapid development of new pharmacologic agents to improve patient outcomes and reduce LOS. A reduction in LOS enables allocation of scarce resources such as the need for freeing hospital beds during a surge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hospital treatment is expensive, and the costs of intensive care amount to around 20% of the total hospital expenditure ( 4 , 5 ). Moreover, during the ICU stay, mechanical ventilation of the lungs could increase the daily costs by additional 26% ( 6 ). In the USA, ventilatory support for a COVID-19 patient lasting longer than 96 hours has an estimated median cost of $ 88 114.…”
Section: Cost-effectiveness Analysesmentioning
confidence: 99%
“…8 Hospitals struggle to have enough ICU beds available for critically ill patients, especially during high peak seasons such as influenza or during pandemics, and ICU costs are a significant component of total health care costs. [9][10][11][12][13] It is essential to establish options for delivering safe and effective respiratory therapy to patients outside the ICU setting.…”
Section: Introductionmentioning
confidence: 99%